The Effects of Endurance Exercise in Hypoxia on Acid-Base Balance, Potassium Kinetics, and Exogenous Glucose Oxidation - Sumi, Daichi; Kasai, Nobukazu; Ito, Hiroto; Goto, Kazushige (Frontiers in Physiology, 2019)
Purpose To investigate the carbohydrate metabolism, acid–base balance, and potassium kinetics in response to exercise in moderate hypoxia among endurance athletes. Methods Nine trained endurance athletes [maximal oxygen uptake (VO2max): 62.5 ± 1.2 mL/kg/min] completed two different trials on different days: either exercise in moderate hypoxia [fraction of inspired oxygen (FiO2) = 14.5%, HYPO] or exercise in normoxia (FiO2 = 20.9%, NOR). They performed a high-intensity interval-type endurance exercise consisting of 10 × 3 min runs at 90% of VO2max with 60 s of running (active rest) at 50% of VO2max between sets in hypoxia (HYPO) or normoxia (NOR). Venous blood samples were obtained before exercise and during the post-exercise. The subjects consumed 13C-labeled glucose immediately before exercise, and we collected expired gas samples during exercise to determine the 13C-excretion (calculated as 13CO2/12CO2). Results The running velocities were significantly lower in HYPO (15.0 ± 0.2 km/h) than in NOR (16.4 ± 0.3 km/h, P < 0.0001). Despite the lower running velocity, we found a significantly greater exercise-induced blood lactate elevation in HYPO compared with in NOR (P = 0.002). The bicarbonate ion concentration (P = 0.002) and blood pH (P = 0.002) were significantly lower in HYPO than in NOR. There were no significant differences between the two trials regarding the exercise-induced blood potassium elevation (P = 0.87) or 13C-excretion (HYPO, 0.21 ± 0.02 mmol⋅39 min; NOR, 0.14 ± 0.03 mmol⋅39 min; P = 0.10). Conclusion Endurance exercise in moderate hypoxia elicited a decline in blood pH. However, it did not augment the exercise-induced blood K+ elevation or exogenous glucose oxidation (13C-excretion) compared with the equivalent exercise in normoxia among endurance athletes. The findings suggest that endurance exercise in moderate hypoxia causes greater metabolic stress and similar exercise-induced elevation of blood K+ and exogenous glucose oxidation compared with the same exercise in normoxia, despite lower mechanical stress (i.e., lower running velocity).